2022
DOI: 10.1007/s10800-022-01687-w
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and stability of 2-mercaptobenzimidazole inhibitor film upon Al alloy 6061

Abstract: Organic corrosion inhibitors have become competent alternatives to hazardous chrome conversion coatings due to their rapid adsorption over metal surfaces in corrosive environments. Literature suggests a wide range of organic corrosion inhibitors with high inhibition efficiency, barrier properties, and adsorption mechanisms. However, the long-term durability and protectiveness of an organic inhibitor film need to be understood with in-depth insights on its interaction with heterogenous alloy surfaces like AA6xx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 118 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…The amphoteric nature of aluminium oxides under high pH conditions could degrade the oxide layers, exposing bulk Al to anodic dissolution. 42 The presence of chloride ions disrupts the stability of the passive layer, potentially reducing the passive range. Conversely, when the solution incorporates an effective inhibitor, it can expand the pH range beyond the typical stability thresholds of aluminium oxide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amphoteric nature of aluminium oxides under high pH conditions could degrade the oxide layers, exposing bulk Al to anodic dissolution. 42 The presence of chloride ions disrupts the stability of the passive layer, potentially reducing the passive range. Conversely, when the solution incorporates an effective inhibitor, it can expand the pH range beyond the typical stability thresholds of aluminium oxide.…”
Section: Resultsmentioning
confidence: 99%
“…For the alloy AA6014, it has been reported that Mg 2 Si acts as an anode due to the anodic corrosion potential of the Al matrix. 6,42 Consequently, these intermetallic particles preferentially dissolve concerning the Al matrix in neutral and acidic conditions. Fig.…”
Section: Msde Papermentioning
confidence: 99%